2022
DOI: 10.1177/03010066221108281
|View full text |Cite
|
Sign up to set email alerts
|

The central-peripheral dichotomy and metacontrast masking

Abstract: According to the central-peripheral dichotomy (CPD), feedback from higher to lower cortical areas along the visual pathway to aid recognition is weaker in the more peripheral visual field. Metacontrast masking is predominantly a reduced visibility of a brief target by a brief and spatially adjacent mask when the mask succeeds rather than precedes or coincides with the target. If this masking works mainly by interfering with the feedback mechanisms for target recognition, then, by the CPD, this masking should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…More evidence along these lines has been reported by Lamme, Zipser, and Spekreijse ( 2002 ) and by Supèr, Spekreijse, and Lamme ( 2001 ), who found that feedback from extrastriate areas was critical for the stimuli to reach consciousness. Furthermore, Zhaoping and Liu ( 2022 ) found that metacontrast masking is weaker for stimuli displayed in the peripheral retina where feedback from higher to lower brain regions is thought to be weaker. Clearly, metacontrast masking cannot be wholly explained in terms of feed-forward processes.…”
Section: Phenomena That Require Between-levels Re-entrant Accountsmentioning
confidence: 99%
“…More evidence along these lines has been reported by Lamme, Zipser, and Spekreijse ( 2002 ) and by Supèr, Spekreijse, and Lamme ( 2001 ), who found that feedback from extrastriate areas was critical for the stimuli to reach consciousness. Furthermore, Zhaoping and Liu ( 2022 ) found that metacontrast masking is weaker for stimuli displayed in the peripheral retina where feedback from higher to lower brain regions is thought to be weaker. Clearly, metacontrast masking cannot be wholly explained in terms of feed-forward processes.…”
Section: Phenomena That Require Between-levels Re-entrant Accountsmentioning
confidence: 99%